Inhibition of Tissue Factor Expression in Brain Microvascular Endothelial Cells by Nanoparticles Loading NF-κB Decoy Oligonucleotides - Wang, Huafang (Molecular Diversity Preservation International (MDPI), 2008)
To investigate a nuclear factor-kappa B decoy oligonucleotides strategy on the inhibition of tissue factor (TF) expression in cultured rat brain microvascular endothelial cells (BMECs) by polylactic acid (PLA) nanoparticles delivery system and to evaluate this new vector for in vitro gene therapy. Nanoparticles were formulated using poly D,L-polylactic acid with surface modifying by polysorbates 80. 3-[4,5-Dimethylthiazol-2,5-diphenyl-2H-tetrazolium bromide] (MTT) assays showed that PLA nanoparticles were not toxic to the cultured BMECs.The decoy oligonuceotides (ODNs) loaded within nanoparticles was 6 μg/mg, encapsulation efficacy was (60.5±1.5)%. It was observed by flow cytometry that the cellular uptake of nanoparticles depended on the time of incubation and the concentration of nanoparticles in the medium. And confocal microscopy demonstrated that nanoparticles localized mostly in the BMECs cytoplasm. The released decoy oligonuceotides (ODNs) uptaked by BMECs retained their biologic activity and led to reduced level of tissue factor expression as compared to control cultures. These findings offer a potential therapeutic strategy in the control of TF expression in BMECs in vitro and suggest that PLA nanoparticles may be appropriate as delivery vehicles for decoy strategy in the gene therapy of cerebral thrombosis.